Machine Scheduling with Deteriorating Jobs and Modifying Maintenance Activities. (14th June 2017) - Wang, Ji-Bo; Li, Lin
Abstract: In this study we consider the problem of scheduling n jobs on m unrelated parallel processors with deterioration effect. We allow an option for performing a modifying (i.e. deteriorating) maintenance activity on each machine, i.e. the job normal processing times will be changed following this modifying maintenance activity. We need to make a decision on when to schedule the modifying maintenance activities and the sequence of jobs so as to minimize a cost function containing total completion (waiting) time, total absolute differences in completion (waiting) times, and total machine load. We show that the problem remains polynomially solvable under the proposed model.